The Role of the SDR in the international monetary system : studies - Roushdy, Juanita; International Monetary Fund.; International Monetary Fund. (Washington, D.C. : The Fund, 1987)
This draft explains the role of special drawing right (SDR) in international monetary system. the study further examines issues raised in the reports of the Group of Ten and the Group of twenty-four on the monetary system.
"March 1987."
Edited by Juanita Roushdy.
Includes bibliographies.
asm; 16/04/19
Loans
Keywords: Special drawing rights; European currency unit; International finance